Euripides"s Helena and Pentateuch traditions: The Septuagint from the perspective of Ancient Greek Tragedies - Daphnē, Euangelia (HTS teologiese studies, 2015)
In some cases discussed below, the present form of the Septuagint is not representative of how Ancient Greek Tragedies were received by the LXX translators, but of how Old Testament traditions in Greek form were received by the tragedians.